2022
DOI: 10.1007/s40263-022-00931-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Depressive Symptoms: Epidemiology, Pathophysiology, and Pharmacological Treatment

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic is still spreading worldwide over 2 years since its outbreak. The psychopathological implications in COVID-19 survivors such as depression, anxiety, and cognitive impairments are now recognized as primary symptoms of the “post-acute COVID-19 syndrome.” Depressive psychopathology was reported in around 35% of patients at short, medium, and long-term follow-up after the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection. Post-COVID-19 depressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
122
1
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 194 publications
14
122
1
9
Order By: Relevance
“…Fatigue is also an important component of MDD and it has been shown that SARS-CoV-2 infection is able to elicit episodes of major depression. 49, 50 Indeed, also in our series we found a prevalence of 23% (HADS-D) and 37% (BDI-12) of depression in the group of long COVID patients with disabling fatigue. Our long COVID patients show monocyte gene expression abnormalities similar as those found in “regular” MDD patients with severe and recurrent depression.…”
Section: Discussionsupporting
confidence: 75%
“…Fatigue is also an important component of MDD and it has been shown that SARS-CoV-2 infection is able to elicit episodes of major depression. 49, 50 Indeed, also in our series we found a prevalence of 23% (HADS-D) and 37% (BDI-12) of depression in the group of long COVID patients with disabling fatigue. Our long COVID patients show monocyte gene expression abnormalities similar as those found in “regular” MDD patients with severe and recurrent depression.…”
Section: Discussionsupporting
confidence: 75%
“…The relevance of depression as a factor associated with chronic pain is supported in the literature [ 48 ]. Additionally, the relevance of depressive symptoms in people with the post-COVID-19 condition is also clear in the literature [ 49 ]. The presence of depressive symptoms has been associated to higher risk of other post-COVID-19 symptoms such as fatigue [ 50 ] or dyspnea [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction between physical and emotional post-COVID-19 symptoms would explain a worse HRQoL experienced by the patients. Potential psychopathological mechanisms underlying depressive symptoms in subjects with the post-COVID-19 condition are mainly related to the inflammation triggered by an exaggerated immune response to the viral acute infection (i.e., cytokine storm) and to the persistent psychological burden during (e.g., severity of the disease, or hospitalization) and after (e.g., isolation, post-traumatic stress, or uncertainty about prognosis) the acute infection [ 49 ]. Since anxiety and depressive symptoms can be present up to several years after the infection [ 51 ], continuous monitoring of this symptom will be important for determining the evolution of HRQoL in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The use of nutraceuticals in post-COVID syndrome is currently under study. Several reports are described in adults [ 66 , 67 ], older people [ 68 ], and children [ 69 , 70 ] for different symptoms including olfactory loss [ 71 ], telogen effluvium [ 72 ], and depression and anxiety [ 73 ].…”
Section: Nutraceuticals and Dietary Supplements Against Covid-19 Dise...mentioning
confidence: 99%